Diseño de un sistema de gestión de procesos en la extracción y producción de aceite rojo de palma africana para la extractora la joya de la provincia de Santo Domingo de los Tsáchilas, para el año 2016 - Sarrias Pantoja, Edgar Enrique (2017)
The present investigation was carried out in the La Joya red palm oil extractor in the canton La Concordia, the general objective is to analyze the influence of the application of processes in the extraction and production of African palm red oil in the aforementioned company. For the development of the research the inductive-deductive method was used with the purpose of bringing the researcher closer to the reality of the company to identify the causes related to the management of processes for the extraction of red oil from African palm in La Joya Extractor. As well as the analytical-synthetic method in order to scientifically substantiate the subject under study. Techniques were used as direct observation in the activities and processes of the company, which was carried out to 8 operators of each shift, interviewing 1 person who is responsible for the area. The instruments for collecting data were based on the structured interview guide applied to the production manager and the observation sheet used in each section of the production area of the La Joya. During the visits to the facilities of the extractor, 3 types of people were identified, one production manager, two shift supervisors, eight operators distributed in each of the equipment or sections. Failure was evident in the application of processes to execute the activities of production and extraction of red palm oil, which was evidenced by unstandardized activities that cause losses in production. Not maintaining the tasks and activities in a regulated way to obtain African red palm oil produces a loss of raw material between the different shifts, starting from the load area that must be done in 8 minutes and shift 1 in 15 minutes and turn 2 in 18 minutes. The sterilization time of the fruit should be done in 50 minutes and turn 1 in 56 minutes and turn 2 in 59 minutes. The time to be used in unloading the sterilizers is 20 minutes, however, turn 1 uses 30 minutes and shift 2 uses 38 minutes. Clarification must have a dilution of 1.30% and turn 1 dilutes 1.33% and turn 2 dilutes 1.36% fruit liquor. data that are evident in the results obtained. The proposal for process management seeks to minimize the deficiency in the execution of activities between the different shifts of work and to reduce losses of raw material due to lack of organization. A manual of processes and control logs was designed to be filled by the operators focused on the reality of the production area of red African palm oil in La Joya Extractor, as a conclusion to be used by the management and operational level of such so that activities and actions are carried out in a standardized way with the purpose of maximizing production and minimizing times to 15 minutes per stop. Finally, the recommendation is the socialization of this research, which will be the responsibility of the author of the research project since it holds the authorship rights and is the one who knows in depth each of the technical components of the process manual, whose implementation budget is 201 ,50 dollars.